Faktor Kompetensi Perencana, Data dan Anggaran pada Efektivitas Perencanaan Penanggulangan Bencana Alam di Kabupaten Sumedang - Dadan Setia Nugraha; Lalas Sulastri (Universitas Medan Area, 2018)
The research method used is descriptive analysis. This method serves to obtain a factual description of the causal relationship between variables through the submission of the proposed hypothesis. Data collection techniques are carried out through literature studies, observations, questionnaires and structured interviews. The study population was all employees at the Badan Penanggulangan Bencana in Sumedang District, namely 198 people. The sampling technique used is proportionate stratified random sampling. the research sample was 50 respondents who were taken randomly. The analysis technique used to test the research hypothesis is multiple linear regression analysis, t-test and F-test, and the coefficient of determination.